Pervasive and non-random recombination in near full-length HIV genomes from Uganda. Issue 1 (11th February 2020) - Grant, Heather E; Hodcroft, Emma B; Ssemwanga, Deogratius; Kitayimbwa, John M; Yebra, Gonzalo; Esquivel Gomez, Luis Roger; Frampton, Dan; Gall, Astrid; Kellam, Paul; de Oliveira, Tulio; Bbosa, Nicholas; Nsubuga, Rebecca N; et al.
Abstract: Recombination is an important feature of HIV evolution, occurring both within and between the major branches of diversity (subtypes). The Ugandan epidemic is primarily composed of two subtypes, A1 and D, that have been co-circulating for 50 years, frequently recombining in dually infected patients. Here, we investigate the frequency of recombinants in this population and the location of breakpoints along the genome. As part of the PANGEA-HIV consortium, 1, 472 consensus genome sequences over 5 kb have been obtained from 1, 857 samples collected by the MRC/UVRI & LSHTM Research unit in Uganda, 465 (31.6 per cent) of which were near full-length sequences (>8 kb). Using the subtyping tool SCUEAL, we find that of the near full-length dataset, 233 (50.1 per cent) genomes contained only one subtype, 30.8 per cent A1 ( n = 143), 17.6 per cent D ( n = 82), and 1.7 per cent C ( n = 8), while 49.9 per cent ( n = 232) contained more than one subtype (including A1/D ( n = 164), A1/C ( n = 13), C/D ( n = 9); A1/C/D ( n = 13), and 33 complex types). K -means clustering of the recombinant A1/D genomes revealed a section of envelope (C2gp120-TMgp41) is often inherited intact, whilst a generalized linear model was used to demonstrate significantly fewer breakpoints in the gag–pol and envelope C2-TM regions compared with accessory gene regions. Despite similar recombination patterns in many recombinants, no clearly supported circulating recombinant form (CRF) was found, there was limited evidence of the transmission of breakpoints, and the vast majority (153/164; 93 per cent) of the A1/D recombinants appear to be unique recombinant forms. Thus, recombination is pervasive with clear biases in breakpoint location, but CRFs are not a significant feature, characteristic of a complex, and diverse epidemic.